EX NIHILO IN AJIDARMA’S SHORT STORY "KERONCONG PEMBUNUHAN" - Kholidah, Uci Elly (PARADIGM: Journal of Language and Literary Studies, 2024)
This study delves into how ex nihilo—a radical departure from the usual order—manifests in Seno Gumira Ajidarma’s short story “Keroncong Pembunuhan,” drawing on Slavoj Žižek’s theory. In this research, the authors conducted a detailed examination of the main character’s moments of crisis and rebellion, revealing that these disruptions transcend personal struggles. Rather, they emerge as significant acts of protest against the societal norms and regulations that exert influence over individual identity and behavior. The analysis does not stop at the story itself, as it also draws on Ajidarma’s background, highlighting parallels between the marksman’s crisis of conscience and the author’s real-life struggles with authority during Indonesia’s New Order Era. Unlike earlier studies that primarily examined inner conflicts or moral dilemmas, this research distinguishes itself by employing Žižek’s ideas to illustrate how radical subjectivity and novel forms of resistance emerge in a contemporary Indonesian novel. The findings demonstrate how ex nihilo becomes a tool for expressing agency and dissent, opening up new ways to consider the connections between literature, ideology, and politics. This study concludes by encouraging further research on Žižek’s theories in the context of Indonesian writing, suggesting how stories can challenge power and envision new forms of subjectivity in the aftermath of authoritarianism.